Infrared Optical Response of Metallic Graphene Nanoribbons - Zigang Duan; Wenhu Liao; Guanghui Zhou (Advances in Condensed Matter Physics)
We investigate theoretically the infrared optical response characteristics of metallic armchair/zigzag-edge graphene nanoribbons (A/ZGNRs) to an external longitudinally polarized electromagnetic field at low temperatures. Within the framework of linear response theory at the perturbation regime, we examine the optical infrared absorption threshold energy, absorption power, dielectric function, and electron energy loss spectra near the neutrality points of the systems. It is demonstrated that, by some numerical examples, the photon-assisted direct interband absorptions for AGNR exist with different selection rules from those for ZGNR and single-walled carbon nanotube at infrared regime. This infrared optical property dependence of GNRs on field frequency may be used to design graphene-based nanoscale optoelectronic devices for the detection of infrared electromagnetic irradiations.